Indicators of Entrepreneurial Behavior and Attitudes for Entrepreneurs of Slovenia and Croatia, in 2018/2019 - Ilic, Milena; Ranković, Marko; Janić, Lazar; Mitić, Branislav (Journal of Economic Development, Environment and People, 2020)
Abstract. Following the theoretical presentation of entrepreneurship, that is, the determinants that determine the success of entrepreneurial ventures extracted from various scientific studies and research, the paper defines through research the indicators of entrepreneurial behavior and attitudes using the Global Entrepreneurship Monitor 2018/2019 Global Report database. Using the methods of comparison, induction and deduction, an analysis of indicators of Entrepreneurial Behavior and Attitudes for Slovenia and Croatia was conducted.